Design of nickel-based heterogeneous catalysts for methane conversion - Ighalo, Joshua Osebhagimede (My University, 2026)
Dry reforming of methane (DRM) and catalytic methane pyrolysis (CMP) are technologies for the valorization of methane to cleaner fuels. DRM is a reaction of methane and carbon dioxide to produce syngas, while CMP is the breakdown of the methane molecule into carbon and hydrogen. Due to the high reaction temperatures and presence of side reactions in DRM, the major challenges are coking, sintering, and selectivity. For CMP, coking and sintering challenges are also pervasive. In this thesis, we employed different innovative strategies based on well rationalized hypothesis to design catalysts to solve these challenges... [See PDF for full abstract]
Keywords: Dry reforming; Methane valorization; Hydrogen production; Metal-support interactions; Exsolution; Graphene